PEMODELAN TINGGI GELOMBANG UNTUK PENENTUAN TINGKAT KERENTANAN PESISIR KABUPATEN SUKABUMI - Taofiqurohman Taofiqurohman (Jurnal Harpodon Borneo, 2013)
Modeling of wave heigh in the coastal of Kabupaten Sukabumi was conducted usingWave Exposure Model program. The aim of this study was to predicting wave heightbased on wind data and to determine vulnerability coastal of Kabupaten Sukabumi to the effects of wave. The results of this study indicate that mean wave high in coastal of Kabupaten Sukabumi variated from 1,21 meter to 1,77 meter. The vulnerability coastal of Kabupaten Sukabumi to the effects of wave categorized on high and very high risk.Keyword : Modeling, Wave heigh, Vulnerability, Coastal of Kabupaten Sukabumi